2017
DOI: 10.1007/s11596-017-1690-3
|View full text |Cite
|
Sign up to set email alerts
|

SLC38A1 promotes proliferation and migration of human colorectal cancer cells

Abstract: Current studies have demonstrated that SLC38A1 proteins play a causal role in neoplastic cell transformation. The twofold aim of this study was to provide insight into whether a variance in the expression of SLC38A1 exists between human colorectal cancer and healthy human tissues and to determine how silencing or overexpressing the SLC38A1 gene could affect the proliferation, viability and migration of colorectal cancer cells. Immunohistochemical staining was used to analyze the expression of SLC38A1 in colore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 23 publications
2
22
0
Order By: Relevance
“…SLC38A1 is a member of the amino acid transport family, and it has been confirmed that the survival time of patients with increased SLC38A1 expression in AML is significantly shorter than that of patients with low expression [ 41 ]. Meanwhile, the high expression of SLC38A1 is closely related to the occurrence, recurrence, and metastasis of solid tumors such as gastric cancer [ 42 ], colon cancer [ 43 ], and cervical cancer, indicating poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…SLC38A1 is a member of the amino acid transport family, and it has been confirmed that the survival time of patients with increased SLC38A1 expression in AML is significantly shorter than that of patients with low expression [ 41 ]. Meanwhile, the high expression of SLC38A1 is closely related to the occurrence, recurrence, and metastasis of solid tumors such as gastric cancer [ 42 ], colon cancer [ 43 ], and cervical cancer, indicating poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…CRC is a complex, multi-step disease with a variety of genetic alterations (15,16). A number of proteins have been described as tumor biomarkers that aid the identification of CRC tumors, including A-kinase anchoring protein 4 (17), X-box binding protein 1 (18) and solute carrier family 38 member 1 (19). However, several different CRC subtypes have been identified, including subtypes based on DNA mismatch repair status, oncogene genotypes, or the consensus molecular subtypes derived from transcriptional profiling; therefore, one biomarker is unlikely to identify all types of colorectal tumor (20).…”
Section: Discussionmentioning
confidence: 99%
“…121 Silencing of SLC38A1 also reduced the growth of colon cancer cell lines and pancreas cancer cell lines. 163,164…”
Section: Role Of Amino Acid Transporters In Cancermentioning
confidence: 99%
“…121 Silencing of SLC38A1 also reduced the growth of colon cancer cell lines and pancreas cancer cell lines. 163,164 These results suggest that amino acid transporters have a significant potential in cancer therapy, but the field lacks, with a few exceptions, highly specific inhibitors that could be used in animal models and clinical trials.…”
Section: Role Of Amino Acid Transporters In Cancermentioning
confidence: 99%